Acute Compartment Syndrome in Type IIIB Open Tibial Shaft Fractures Using a 2-Stage Orthoplastic Approach. Issue 12 (December 2021) - Al-Hourani, Khalid; Stoddart, Michael; Pearce, Oliver; Riddick, Andrew; Khan, Umraz; Kelly, Michael B.
Abstract : Objective: To determine the rate of acute compartment syndrome (ACS) in a series of patients with Gustilo–Anderson type IIIB open tibial shaft fractures that were treated using a specific 2-stage orthoplastic protocol. Design: Consecutive cohort study. Patients/Participants: Ninety-three (n = 93) consecutive patients with a type IIIB open tibial shaft fracture (OTA/AO-42) treated using a 2-stage orthoplastic approach, between August 2015 and January 2018. After exclusions, 83 (n = 83) were eligible for analysis. Intervention: Colloid resuscitation and 2-stage orthoplastic reconstruction of type IIIB open tibial shaft fracture. Stage 1 consists of "3-vessel view" early debridement and temporary internal fixation, with stage 2 consisting of a single-stage fix and flap. Main Outcome Measurements: Rate of ACS. Secondary outcomes included early/late sequelae of missed ACS, deep infection, arterial injury, nonunion, and flap failure. Results: Eighty-three (n = 83) patients were included for analysis. The median age was 45.4 years [interquartile range (IQR) 35] with a median follow-up of 1.6 years (IQR 0.8). The median number of operations was 2.0 (IQR 4). For the primary outcome, there were a total of 0 (0/83) patients who required fasciotomy or developed early/late clinical sequelae of missed ACS. Six (6/83, 7.2%) patients developed deep infection, 18 patients (18/83, 21.7%) experienced nonischemic arterial injury, 5 patients (5/83, 6.0%) experienced nonunion, with 4 patients (4/83, 4.8%) experiencing flap failure. Diabetes was the only variable associated with deep infection ( P = 0.025) and nonunion ( P < 0.001). Conclusions: Patients with type IIIB open tibial shaft fractures treated with colloid resuscitation and a 2-stage orthoplastic protocol, which includes early "3-vessel view" exposure and debridement, do not appear to develop ACS. Furthermore, no sequelae of missed compartment syndrome was observed at final follow-up. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.